Pengaruh Brand Image, Kualitas Produk dan Variasi Produk terhadap Keputusan Pembelian Produk Skincare Lacoco di Kota Batam - Rahmawati, Enjelina; Suhardi, Suhardi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Lacoco, a local skincare brand in Indonesia, is facing challenges in building a strong market presence amid intense competition from more established brands. Despite offering products with natural ingredients and functional benefits, its purchasing rate remains relatively low. This study aims to examine the influence of brand image, product quality, and product variation on consumer purchasing decisions for Lacoco skincare products in Batam City. A quantitative approach with a descriptive design was employed. Due to an unknown population size, the sample of 100 respondents was selected using the Lameshow formula and purposive sampling based on specific criteria. Data analysis involved validity and reliability testing, classical assumption tests, multiple linear regression, coefficient of determination (R²), and hypothesis testing using t-tests and F-tests. The findings reveal that brand image has a significant positive effect on purchasing decisions with a contribution of 27.6%, product quality contributes 24.2%, and product variation shows the highest influence at 43.0%. Collectively, the three variables explain 61.1% of the variation in consumer purchasing decisions, while the remaining 38.9% is attributed to other factors outside the model. These results indicate that strengthening brand image, improving product quality, and expanding product variety are key strategies to enhance consumer decisions in favor of Lacoco.